1984
DOI: 10.1007/bf01656024
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and operative diagnosis of pancreatic cancer

Abstract: The aim of the investigation in the case of pancreatic cancer is to establish the diagnosis and to evaluate resectability. Improved diagnostic methods have made it possible in most cases to diagnose accurately the symptomatic patient with pancreatic cancer. Ultrasonography, computed tomography, endoscopic retrograde cholangiopancreatography (ERCP), and cytology are methods that often complement each other in the diagnostic workup. Percutaneous transhepatic cholangiography (PTC) is useful in the jaundiced patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In addition, pancreatic resections are also sometimes performed for complicated chronic pancreatitis. 10 Resectability is typically determined by the surgeon at the time of surgery by assessing for possible metastasis and vascular involvement, 34,35 with advanced imaging less reliable. 36,37 Frozen section has proven to be useful, especially when positive 15 and when additional intraoperative findings, not previously documented with imaging studies, are observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pancreatic resections are also sometimes performed for complicated chronic pancreatitis. 10 Resectability is typically determined by the surgeon at the time of surgery by assessing for possible metastasis and vascular involvement, 34,35 with advanced imaging less reliable. 36,37 Frozen section has proven to be useful, especially when positive 15 and when additional intraoperative findings, not previously documented with imaging studies, are observed.…”
Section: Discussionmentioning
confidence: 99%